THE EFFECT OF TOURIST PRODUCTS ON VISITOR SATISFACTION AT THE STATE MUSEUM OF NORTH SUMATRA PROVINCE - Bancin, Desmianta; Maulidina (Jurnal Ekonomi, 2022)
Museums are cultural tourist attractions that provide education, which introduces historical relics that will certainly awaken the spirit of nationalism and add knowledge. The State Museum of North Sumatra Province provides visitor satisfaction with the attraction of objects and writings containing the history of the North Sumatra region. Not only that, the Museum also provides clean and comfortable facilities, plus access to visit the museum can also be reached by public and private transportation. The location in the middle of the city is quite strategic. The results showed that the attractiveness provided was significantly to the satisfaction of visitors to come The calculated t value for the Attractiveness variable (X1) of 2.229 is greater than the t table 2.020 (2.229>2.020) or the sig.t value for the Attractiveness variable 0.031 is smaller than 0.05 (0.031<0.05). Likewise with facilities where the t-count for the Facility variable (X2) is 4,199 greater than the t table 2,020 (4,199>2,020), or the sig.t value for the Facility variable 0.000 is less than 0.05. this means that the facility has a significant effect on visitor satisfaction for accessibility has a positive and significant effect on visitor satisfaction to the State Museum of North Sumatra Province. The calculated t value for the Accessibility variable (X3) is 4,060 greater than the t table 2,020 (4,060>2,020), or the sig.t value for the Accessibility variable 0.000 is less than 0.05. this means that Accessibility has a significant effect on visitor satisfaction Simultaneously, Attractiveness, Facilities and Accessibility have a positive and significant effect on visitor satisfaction at the North Sumatra State MuseumThis study used three variables, namely two free variables, and one bound variable, where Facilities (X1), Tourist Attraction (X2) are free variables, while visiting interests (Y) as bound variables. The tests used in, this study are reliability test, normality test, multicholinearity test, heteroskedasity test, coefficient determination (R2), Test (t), Test (F).